Metalated Indoles, Indazoles, Benzimidazoles, and Azaindoles and Their Synthetic Applications - Ila, Hiriyakkanavar; Markiewicz, John T.; Malakhov, Vladimir; Knochel, Paul (Synthesis, 2013)
This review focuses on the regioselective metalation of condensed azoles, such as indole, indazole, benzimidazole, 4-, 5-, 6-, and 7-azaindole. The metalation strategies discussed include halogen–metal exchange, metal insertion into carbon–halogen bonds, and directed deprotonation. The influence of different nitrogen-protecting groups and directed metalating groups is discussed. This review covers literature published mainly from 1991 to 2010.1 Introduction2 Metalation of Indoles2.1 C2-Metalation of Indoles2.2 C3-Metalation of Indoles2.3 C4–C7-Metalation of Indoles3 Metalation of Indazoles4 Metalation of Benzimidazoles5 Metalation of Azaindoles6 Conclusion
Keywords: metalation; indoles; heterocycles; cross-coupling; natural products